Multivariate analysis of factors related to the absence of musculoskeletal degenerative disease in middle‐aged and older people. Issue 11 (20th November 2019) - Imagama, Shiro; Ando, Kei; Kobayashi, Kazuyoshi; Machino, Masaaki; Tanaka, Satoshi; Morozumi, Masayoshi; Kanbara, Shunsuke; Ito, Sadayuki; Inoue, Taro; Seki, Taisuke; Ishizuka, Shinya; Nakashima, Hiroaki; et al.
Abstract : Aim: Musculoskeletal degenerative disease (MSD; osteoporosis, knee arthritis and lumbar spondylosis) decreases the quality of life (QOL) of older people. The objective of the present study was to identify the factors related to the absence of MSD in multivariate logistic regression analysis. Methods: The participants were 1034 volunteers (444 men, 590 women, mean age 63.5 years) in the Yakumo study. Osteoporosis (percentage of young adult mean ≤70%), knee arthritis (Kellgren–Lawrence grade ≥2), and lumbar spondylosis (Nathan class ≥3) were prospectively examined. Participants were divided into those with and without MSD. Age, sex, body mass index, muscle strength, gait ability, pain, body balance, spinal sagittal alignment, geriatric syndrome (locomotive syndrome, frailty and sarcopenia) and QOL (Short Form Health Survey) were compared between these groups to identify the factors associated with the absence of MSD. Results: Significantly lower age, body mass index and pain; higher gait speed, grip and back muscle strength; more stable body balance; better sagittal spinal alignment; and lower rates of locomotive syndrome, frailty and sarcopenia were observed in the group without MSD ( n = 445, 43%), with significantly better QOL ( P  < 0.0001). In multivariate logistic regression analysis adjusted for age and sex, lower body mass index (odds ratio [OR] 1.10, P  < 0.001), lower spinal inclination (OR 1.08, P  < 0.01), higher back muscle strength (OR 1.01, P  < 0.05), no locomotive syndrome (OR 1.80, P  < 0.05) and good body balance (OR: 1.12, P  < 0.05) were significant factors for the absence of MSD. Conclusions: Factors related to an absence of MSD are also related to good QOL, and should be a focus of health interventions in healthy middle‐aged and older people. Geriatr Gerontol Int 2019; 19: 1141–1146 .